Accuracy of Risanto's Formula Compared with Johnson's to Estimate Fetal Weight in Overweight Mothers - Noviana, Fifi; Siswosudarmo, Risanto; Hadiati, Diah Rumekti (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2016)
Background: Estimated fetal weight (EFW) is becoming important because it is used as a guidence for determining mode of delivery. The use of estimated fetal weight based on fundal height has been widely used, but its use in overweight pregnant mothers was still limitted.Objective: To compare the accuracy of Risanto’s and Johnson’s formulas in estimating fetal weight based on fundal height in overweight mothers.Method: It was a cross-sectional study, conducted from March 2013 to July 2014 in Sardjito hospital and hospital networks. All pregnant mothers meeting the elligibility criteria were used as study subjects. Overweight mother was defined based on body mass index (BMI) and skinfold thickness on suprailiaca region. Fundal height (FH) was measured from the symphysis pubis to the midle of the upper border of the pregnant uterus. Accuracy of Risanto’s and Johnson’s formulas was dtermined by comparing the difference between EFW and actual infant birth weight (AIBW). Paired t-test was used for statistical analysis.Result and Discussion: There were 395 overweight pregnant mothers fulfilling the inclusion and exclusion criteria. The mean AIBW was 3060.3 ± 322.5 grams (ranged from 2360 to 3940 grams). The mean EFW using Risanto formula (R_EFW) was 3095.8 ± 320.3 grams (ranged from 2370 to 3870 grams ) while that of Johnson (J_EFW) was 3273,7 ± 378,1 grams (ranged from 2325 to 4185 grams). The mean difference between between AIBW and ∆R) EFW (was 109.85 grams while that of AIBW and J_EFW∆J) (was 198.41 grams ∆.RIt was clear that significantly smaller ∆J than with the mean difference minus 88.56 grams (95% CI -98.76 to -78.35; p value 0.000).Conclusion: The new Risanto’s formula was more accurate to estmate infant birth weight than Johnson’s in overweight mothers.Keywords: Risanto’s and Johnson’s Formulas, Estimated Fetal Weight, Overweight Mothers.